Toward a unified understanding of climate anxiety: Examining measures of climate and eco-anxiety - Lisa Marie Hempel; Mattis Geiger; Cornelia Betsch (PLoS ONE, 2025)
Despite recent research efforts to understand climate anxiety, related measurement is challenged by multiple definitions and the emergence of several seemingly similar measures, warranting a thorough and joint investigation of their validity. This study (N = 1003) examined the factor structure of existing measures, namely the Climate Anxiety Scale (CAS) and the Hogg Eco-Anxiety Scale (HEAS), and tested their overlap in joint measurement models. The results showed that CAS and HEAS indeed seem to capture the same overarching construct, climate anxiety. A joint measurement model with a single higher-order general factor indicated by a CAS g-factor and four HEAS factors had good fit. This overarching climate anxiety factor was related to but still distinct from nomologically related constructs (e.g., climate-related risk perception, neuroticism). Climate anxiety was also strongly correlated with political participation, an aspect of the readiness for climate action. A small correlation with self-efficacy to show individual emission-reducing behavior and no association with climate-change-related fatigue suggests that high levels of climate anxiety are not accompanied by paralysis but instead by mild activation. The results showed generally low levels of climate anxiety in the general population. These findings are discussed regarding the resulting challenges for validation efforts and experimental work, accompanied with recommendations for further steps in measurement development.